Biased Random Walk by Stochastic Fluctuations of Chemoattractant-Receptor Interactions at the Lower Limit of Detection - van Haastert, Peter J.M. (The Biophysical Society, 2007)
Binding of ligand to its receptor is a stochastic process that exhibits fluctuations in time and space. In chemotaxis, this leads to a noisy input signal. Therefore, in a gradient of chemoattractant, the cell may occasionally experience a “wrong” gradient of occupied receptors. We obtained a simple equation for P(pos), the probability that half of the cell closest to the source of chemoattractant has higher receptor occupancy than the opposite half of the cell. P(pos) depends on four factors, the gradient property [Formula: see text] the receptor characteristic [Formula: see text] a time-averaging constant I, and nonreceptor noise σ(B). We measured chemotaxis of Dictyostelium cells to known shallow gradients of cAMP and obtained direct estimates for these constants. Furthermore, we observed that in shallow gradients, the measured chemotaxis index is correlated with P(pos), which suggests that chemotaxis in shallow gradients is a pure biased random walk. From the observed chemotaxis and derived time-averaging constant, we deduce that the gradient transducing second messenger has a lifetime of 2–8 s and a diffusion rate constant of ∼1 μm(2)/s. Potential candidates for such second messengers are discussed.